Dressler's syndrome: are we underdiagnosing what we think to be rare?. Issue 5 (21st May 2019) - Campos, Isabel Durães; Salgado, Alberto; Azevedo, Pedro; Vieira, Catarina
Abstract : A 46-year-old man was admitted to the emergency department with fever and pleuritic thoracic pain. Six weeks prior to admission, the patient had undergone cardiac surgery. The ECG showed diffuse ST segment elevation and PR segment depression. The blood tests revealed increased inflammatory markers and negative myocardial necrosis markers. Pericardial and left-sided pleural effusion were noted. Sterile blood cultures were negative. Hence, the hypothesis of Dressler's syndrome was established. The patient improved clinically and analytically with a short course of anti-inflammatory therapy and was discharged with colchicine and acetylsalicylic acid. A thoracic radiography performed 2 months after showed complete remission of pleural effusion.